Assessing the Use of Artocarpus heterophyllus Seed Powder at Household Level to Treat Spring Water - Christine Yiga Nansamba (Uganda Christian University, 2025)
The purpose of this research was to assess the potential use of jackfruit (Artocarpus heterophyllus) seed powder as a household-based natural improvement in the quality of spring water in Nakonge communities of Uganda. The investigation was prompted by the continuing consumptions of contaminated and untreated water in the communities which have led to rising rates of waterborne illness. Clean drinking water continues to be a challenge in rural, under-resourced communities, leading to calls for the need to introduce solutions which are affordable, accessible, and sustainable. The study evaluates jackfruit seed powder for its purification (antimicrobial and cleaning) capabilities in terms of efficacy to reduce contaminants and improve water quality. The specific research results show that jackfruit seed powder significantly reduced microbial loads and impurities in spring water. The study also confirmed the ability of jackfruit seed powder to effectively remove contaminants depended on the size of the seed powder and the extraction methodology; finer powder appeared to remove unwanted contaminants at a greater efficacy, in part because of greater surface area are extracted, and lengthening the extraction time (especially the extraction in non-filtered water) encouraged further extraction and release of purification compounds. The proposed framework was intended to be easy to implement and inexpensive, so that local families can adopt the approach using household tools and materials. A treatment system could be created in which spring water was filtered through jackfruit seed powder prior to consumption. Despite some positive outcomes, the study recognizes a few challenges and limitations, such as standardizing and evaluating powder preparation and dosage, and ensuring safety of the treated water
Uundergraduate